Dieta de la zorra gris Urocyon cinereoargenteus y su contribución a la dispersión de semillas en la costa de Oaxaca, México - Villalobos Escalante, Alejandra; Buenrostro-Silva, Alejandra; Sánchez-de la Vega, Guillermo (THERYA, 2014)
Introduction: An important number of mammals of the order Carnivora are opportunists that consume primarily small mammals, although they can amplify their diet with other larger vertebrates and arthropods. Fruits have also been reported in the diet of some carnivores; however, their role as agents of seed dispersal has not been well documented thus far. In this study we analyzed the diet of the grey fox in tropical deciduous forest in the state of Oaxaca throughout the annual seasons, establishing composition and seasonal variation, and determined if seed ingestion contributed to seed dispersal, and therefore favoring germination. Methods: A total of 75 fresh grey fox feces were identified and quantified to determine composition and number of seeds at the Jardín Botánico Regional Puerto Escondido (JBPE) in the coastal region of Oaxaca, Mexico. Identification and quantification of feces composition was based on a presence/absence analysis and then establish frequencies and percentages of food categories, and proportion and germination speed of ingested seeds. Results: Food categories reported in feces were as follow: seeds in 56 of 75 feces representing 74.67%, vertebrates in 45 feces (60%) and invertebrates in 40 feces representing 53.33%. Diet variation was observed by season and by moth, and trophic niche breath varied significantly between seasons (Fig. 1). Identified seeds belonged to seven species. Additionally, germination percentages of the seeds of these species through endozoochory were higher than those obtained from the control seeds (Table 1). Discussion and conclusion: The grey fox is a legitimate seed disperser that consequently generates a positive effect on rates and speed of germination of the utilized species. Furthermore, seasonal variation of seed presence observed in feces is influenced by availability of these seeds in the environment; which puts on evidence the high level of adaptability by this carnivore. Key words: Niche breath, disperser, diet, opportunist, germination percentage, seasonal variation.